Modelling of cementitious backfill interactions with vitrified intermediate-level waste. (June 2017) - Baston, Graham; Heath, Timothy; Hunter, Fiona; Swanton, Stephen
Abstract: New types of wasteform are being considered for the geological disposal of radioactive intermediate-level waste (ILW) in the UK. These include vitrified ILW products arising from the application of thermal treatment processes. For disposal of such wasteforms in a geological disposal facility, a range of concepts are under consideration, including those with a high-pH cementitious backfill (the NRVB, Nirex Reference Vault Backfill). Alternatively, a cement-based material that buffers to a less alkaline pH could be used (an LPB, Low-pH Backfill). To assess the compatibility of these potential new wasteforms with cement-based disposal concepts, it is necessary to understand their impacts on the long-term evolution of the backfill. A scoping thermodynamic modelling study was undertaken to help understand the possible effects of these wasteforms on the performance of the backfill. The model primarily considers the interactions occurring between the vitirified waste, the porewater and the backfill, within a static and (in most cases) totally closed system. The approach was simplified by assuming equilibrium between the backfill and the corroded glass available at selected times, rather than involving detailed, reactive transport modelling. The aim was to provide an understanding of whether the impacts of the vitrified wastes on backfill performance are sufficient to compromise disposal in such environments. The calculations indicated that for NRVB, the overall alkaline buffering capacity of the backfill is not expected to be impaired by interactions with vitrified waste; rather the buffering will be to less alkaline pH values (above pH 9) but for a longer period. For the LPB, slightly lower pH values were predicted in some cases. The sorption capacities of the backfills are unlikely to be impaired by interactions with vitrified ILW. Indeed they may be increased, due to the additional C-S-H phase formation. The results of this study suggest that disposal of vitrified ILW in a cement-based disposal system with a high-pH backfill is a potentially viable disposal option. Highlights: Modelling of chemical interactions between vitrified ILW and cementitious backfills. Evolution of pH, porosity, sorption capacity and mineralogy of the backfill. Impact of calculated evolution on backfill performance evaluated. Vitrified ILW disposal is potentially compatible with a cementitious backfill.